2008
DOI: 10.1103/physrevlett.101.070502
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Correlation without Classical Correlations

Abstract: We show that genuine multiparty quantum correlations can exist on its own, without a supporting background of genuine multiparty classical correlations, even in macroscopic systems. Such possibilities can have important implications in the physics of quantum information and phase transitions.Quantum and classical correlations lie at the heart of sciences and technologies. The emerging quantum technology crucially depends on correlations that are different and more subtle than the ones in classical physics. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 33 publications
2
86
0
Order By: Relevance
“…This behavior is quite general: we have demonstrated it for several values of the parameter Γ 12 , as shown in Appendix C. In Ref. [9], it was shown that only with three or more qubits can one have states with genuine quantum correlations but no classical correlations. Our example does not contradict that general result, since for the two-qubit system here considered the classical correlations, as defined in [8], are indeed different from zero, but it also shows that the same correlations, even though not vanishing, may be much smaller than the quantum correlations, even for a two-qubit system.…”
Section: B Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…This behavior is quite general: we have demonstrated it for several values of the parameter Γ 12 , as shown in Appendix C. In Ref. [9], it was shown that only with three or more qubits can one have states with genuine quantum correlations but no classical correlations. Our example does not contradict that general result, since for the two-qubit system here considered the classical correlations, as defined in [8], are indeed different from zero, but it also shows that the same correlations, even though not vanishing, may be much smaller than the quantum correlations, even for a two-qubit system.…”
Section: B Resultsmentioning
confidence: 68%
“…In Ref. [9], the existence of genuine classical correlations was associated to the non-vanishing of n-party correlation functions involving local observables of the system. Based on this definition, it was shown that it is possible to have multiparty entangled states with no genuine classical correlations, as long as the number of parties is larger than two [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for general two-qubit mixed states, the situation is more complicated. Qubit-qubit entanglement has been characterized and quantified completely whereas quantum discord only for particular Quantum discord for a two-parameter class of states in 2 ⊗ d quantum systems 3 cases [17,18,19,20,21,22,23,24,25,26]. We slightly extend and generalize some of the previous studies to analytically compute the classical correlation and quantum discord for a two-parameter class of states in 2 ⊗ d quantum systems with d ≥ 3.…”
Section: Introductionmentioning
confidence: 99%
“…One might expect that genuinely n-partite entanglement gives rise to non-vanishing correlations between all n subsystems. This is incorrect, at least when correlations are quantified as average values of a product of local measurement results [3,4] (for a discussion on quantum correlations without classical correlations, see e.g. [5]).…”
mentioning
confidence: 99%